The Scope of JIT Implementation in India SMES (International Journal of Food and Nutritional Sciences, 2022)
In the face of global competition, the need of customers demands from the companies to improve the product quality and customer service. The reduction of wastage has long been used by the manufacturing sector as a means to reduce costs and improve the product quality. It is perceived that Just-In-Time (JIT) is highly beneficial in manufacturing industry. However recent studies revealed that service industries are improving their operations using JIT. The operations and activities in many service systems are sequentially similar to activities in manufacturing system. But there is a need to assess the critical elements of just in time specific to service industries. In this paper, the critical elements of the JIT in the context of Indian service industries were identified using a mail survey approach. The questionnaire was sent to the 60 service industries and 30industries responded. On the basis of the responses, critical elements were identified. Attempts have been made to examine the degree of importance and degree of difficulties of these critical elements in Indian service industries. Amatrix has been suggested to branch off the difficult and important elements. The results revealed that JIT plays important role in service industries. It is suggested that the elements which are less difficult but more important should be implemented at the initial stage.